2011
DOI: 10.1007/s00415-011-5994-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with rituximab in patients with polyneuropathy with anti-MAG antibodies

Abstract: Efficacy of rituximab (RTX), a monoclonal anti-CD20 antibody, has been suggested in a recent controlled trial in polyneuropathies with antibodies against myelin-associated glycoprotein (PN-MAG) [1]. Aims of this study were to evaluate the efficacy and safety of RTX in PN-MAG and to search for predictive factors of response to treatment.Six patients fulfilling diagnosis criteria for PN-MAG [2] received four weekly infusions of RTX (375 mg/m 2 ). Clinical status of each patient was evaluated, before treatment (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“… 3 While these symptoms tend to gradually worsen over time, the available treatments, including corticosteroids, immunosuppressive therapies (ISTs), intravenous immunoglobulin (IVIG), and rituximab, were found to have inadequate efficacy compared with other immune-mediated neuropathies. 4 5 6 7 8 9 10 11 12 13 14 15 None of the eight randomized clinical trials (RCTs) on these treatments obtained significant or clinically meaningful results. 7 Although rituximab, an anti-CD20 monoclonal antibody, holds promise as a therapeutic option for anti-MAG neuropathy, it was effective on only 30%–50% of recipients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 While these symptoms tend to gradually worsen over time, the available treatments, including corticosteroids, immunosuppressive therapies (ISTs), intravenous immunoglobulin (IVIG), and rituximab, were found to have inadequate efficacy compared with other immune-mediated neuropathies. 4 5 6 7 8 9 10 11 12 13 14 15 None of the eight randomized clinical trials (RCTs) on these treatments obtained significant or clinically meaningful results. 7 Although rituximab, an anti-CD20 monoclonal antibody, holds promise as a therapeutic option for anti-MAG neuropathy, it was effective on only 30%–50% of recipients.…”
Section: Introductionmentioning
confidence: 99%
“… 24 26 27 Although anti-MAG antibody titers have some value in monitoring the disease, they are not correlated with the disease severity, clinical phenotype, or prognosis. 10 20 21 28 Several serum biomarkers and neurophysiological tests have been explored, such as nerve conduction studies (NCSs). Amaador et al 29 found no clinical utility of neurofilament light chain, contactin-1, or complement activation products.…”
Section: Introductionmentioning
confidence: 99%